SHARIA ECONOMIC LAW ON STOCK INVESTMENT IN THE CAPITAL MARKET - Iman hikmat Nugraha; Zulqarnain; Erry Setiawan (CV. Adiba Aisha Amira, 2025)
This study aims to analyze and evaluate the implementation of Islamic economic law on stock investment in the capital market. In this context, religious economic rules serve to ensure that investing activities take place in accordance with the principles of the teachings that include fairness, transparency, as well as the prohibition of interest (riba) and uncertainty (gharar). Through clear and strict regulations, Islamic economic law is able to provide a sense of security for Muslim investors so that they can contribute without violating religious rules. On the other hand, these rules also provide confidence and stability for all capital market players. The implementation of Islamic economic law encourages companies that want to be listed in the Islamic stock market to have good management and a solid financial structure. Such companies must comply with various provisions, such as limits on the use of loans and adherence to business ethics set out in sharia principles. This compliance is not only beneficial to investors but also improves the quality and discipline of corporate finance, which in turn strengthens the overall integrity and efficiency of the capital market. However, the process of implementing Islamic economic law is not free from challenges. Effective supervision and adequate education for all stakeholders are key to addressing the growing complexity of the market. Strong support from regulators, policy innovation, as well as the application of modern technology are needed to ensure the long- term effectiveness of these rules. Thus, Islamic stock investment can continue to increase and make a positive contribution to the national economy while maintaining sharia principles and improving the welfare of the wider community.